Point-of-Care Diagnostics: Recent Advances and Trends - Vashist, Sandeep (Biosensors (Basel), 2017)
Recent years have witnessed tremendous advances in point-of-care diagnostics (POCD), which are a result of continuous developments in biosensors, microfluidic, bioanalytical platforms, assay formats, lab-on-a-chip technologies, and complementary technologies. This special issue targets the critical advances in POCD and provides guided insights and directions for future research.